REPRESENTASI VISUAL RAJA YOGYAKARTA DALAM SEKAT POLITIK IDENTITAS (ANALISIS SEMIOTIKA GAMBAR RAJA MATARAM) - Andri Prasetyo Yuwono (Jurnal Ilmu Komunikasi AKRAB, 2018)
Visual works are not only autonomous objects, stand alone and interpreted without involving other elements who have an association with them. Images as visual works can be interpreted as a sign, more broadly, the sign is part of a sign system where its existence becomes part of a wider sign system. Representation is the embodiment of the express or implied meaning of each attribute inherent in the visual appearance of an image. The meaning that gives rise to a representation is absolutely necessary for other texts that are interwoven and able to be a benchmark in constructing a representation. These visual texts are the main guideline in the semiotic analysis process that leads to the construction of representation. Sultan Hamengku Buwono for Javanese people is not only seen as a ruler over a region, but more than that. Referring to the visual display that was officially released by the Yogyakarta Palace, the King of Mataram was presented as a role model and power to lead his people towards a balance of body and soul. The king of Mataram, as an entity, was visually raised to the with attributes that were considered capable of representing his function as ruler.Broadly speaking, the discussion in the construction of Sultan Hamengku Buwono's representation will be discussed through three focus discussions. The focus of the discussion is; The Dynamics of Visualization of Sultan Hamengku Buwono, Pose and Power Construction in the Political Identity Session, Clothing as Identity Politics.